Quantifying the sensitivity of the network structure and properties from simultaneous measurements during photopolymerization. Issue 21 (15th May 2017) - Sarkar, Swarnavo; Baker, Paula J.; Chan, Edwin P.; Lin-Gibson, Sheng; Chiang, Martin Y. M.
Abstract : Simultaneous multiparametric measurements are used to capture the relaxation time growth of a photocuring network and quantify crosslink distribution. Abstract : We present a method that combines experimental and computational approaches to assess a comprehensive set of structural and functional evolution during a network formation process via photopolymerization. Our work uses the simultaneous measurement of the degree of conversion, polymerization stress, the change in reaction temperature, and shrinkage strain in situ . These measurements are combined with the theory of viscoelastic materials to deduce the relaxation time and frequency-dependent modulus of the polymerizing network. The relaxation time and degree of conversion are used to demonstrate the effect of processing parameters ( e.g. curing protocol adjusted by the light intensity) in creating different network structures for the same initial resin. We describe experimental trends using effective medium calculations on a cross-linked polymer network model. In particular, we show that the effect of curing conditions on the spatial heterogeneity in crosslink density can be quantified using multiparametric measurements and modeling. Collectively, the present method is a way to examine holistically the complex structural and functional evolution of the network formation process.